Enhancing Fourth-Grade Students' Logical Thinking in Mathematics Through Interactive Math Board Learning Media - Wulandari, Fitri; Relmasira, Stefanus Christian (Papanda Publisher, 2025)
Mathematics education faces significant challenges in developing students' logical thinking abilities, as evidenced by Indonesia's below-average PISA performance. Traditional lecture-based instruction fails to engage students effectively, necessitating innovative interactive learning media to enhance mathematical reasoning capabilities. This study aimed to develop and evaluate the effectiveness of Math Board learning media for improving fourth-grade students' logical thinking abilities in whole number concepts up to 10,000. This research employed a Research and Development approach integrating the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation) with pre-experimental design using pretest-posttest comparisons. Twenty-eight fourth-grade students from SD N Mangunsari 03 participated in the study. Data collection utilized logical thinking ability tests, classroom observations, and structured interviews. Expert validation assessed media quality, while statistical analysis using SPSS version 25 included normality testing, homogeneity testing, paired samples t-test, and N-Gain score analysis to measure improvement effectiveness. Expert validation yielded a quality score of 90.67%, categorizing the Math Board as